Water-soluble CO-releasing molecules reduce the development of postoperative ileus via modulation of MAPK/HO-1 signalling and reduction of oxidative stress. Issue 3 (20th November 2008) - De Backer, O; Elinck, E; Blanckaert, B; Leybaert, L; Motterlini, R; Lefebvre, R A
Abstract : Background and aims: Treatment with carbon monoxide (CO) inhalation has been shown to ameliorate postoperative ileus (POI) in rodents and swine. The aim of this study was to investigate whether CO liberated from water-soluble CO-releasing molecules (CO-RMs) can protect against POI in mice and to elucidate the mechanisms involved. Methods: Ileus was induced by surgical manipulation of the small intestine (IM). Intestinal contractility–transit was evaluated by video-fluorescence imaging. Leucocyte infiltration (myeloperoxidase), inflammatory parameters (ELISA), oxidative stress (lipid peroxidation), and haem oxygenase (HO)/inducible nitric oxide synthase (iNOS) enzyme activity were measured in the intestinal mucosa and muscularis propria. Results: Intestinal contractility and transit were markedly restored when manipulated mice were pre-treated with CO-RMs. Intestinal leucocyte infiltration, expression levels of interleukin 6 (IL6), monocyte chemoattractant protein-1 and intercellular adhesion molecule-1, as well as iNOS activity were reduced by treatment with CORM-3 (a transition metal carbonyl that releases CO very rapidly); whereas expression of IL10/HO-1 was further increased when compared to nontreated manipulated mice. Moreover, treatment with CORM-3 markedly reduced oxidative stress and extracellular signal-related kinase (ERK)1/2 activation in both mucosa (early response) and muscularis (biphasic response). The p38 mitogen-activated protein kinase inhibitor SB203580 abolished CORM-3-mediated HO-1 induction. The HO inhibitor chromium mesoporphyrin only partially reversed the protective effects of CORM-3 on inflammation/oxidative stress in the muscularis, but completely abrogated CORM-3-mediated inhibition of the early "oxidative burst" in the mucosa. Conclusions: Pre-treatment with CO-RMs markedly reduced IM-induced intestinal muscularis inflammation. These protective effects are, at least in part, mediated through induction of HO-1, in a p38-dependent manner, as well as reduction of ERK1/2 activation. In addition, CORM-induced HO-1 induction reduces the early "oxidative burst" in the mucosa following IM.